Household chaos and preschool migrant children’s self-regulation: the mediating role of parent–child conflict and the moderating role of mindful parenting - Zhu, Huihui; Shu, Lina; Wang, Xiaoying; Xu, Zhechuan (Frontiers in Psychology, 2025)
Self-regulation is a foundational ability for children’s learning and socioemotional development. Household chaos, as an unavoidable physical environmental risk in the early growth environment of preschool migrant children, may significantly threaten the development of children’s self-regulation. Therefore, this study, based on the Family Stress Model and the Risk-Protective Factor Model, explores how household chaos affects the self-regulation of preschool migrant children through parent–child conflict and how mindful parenting moderates this relationship. Nine hundred and forty Chinese preschool migrant children and their families participated in this study. The results indicated that after controlling for factors including gender, age, and family socioeconomic status, household chaos was significantly negatively associated with children’s self-regulation ability. Parent–child conflict mediated the relationship between household chaos and the self-regulation of preschool migrant children. At the same time, mindful parenting modified the adverse effects of parent–child conflict on self-regulation, but as the level of parent–child conflict increased, its protective effect gradually decreased. These results suggest that household chaos and parent–child conflict are important risks for the early development of self-regulation in preschool migrant children. In addition, mindful parenting reduced the tension arising from parent–child conflict. These findings underscores the importance of addressing environmental stressors and promoting positive parent–child relationship in early childhood. Moreover, the results provide important implications for both practice and research.